NOVEL PRE-DECOMMISSIONING SELECTION TOOLKIT FOR FIXED OFFSHORE PLATFORMS IN MALAYSIA - NA, KAI LUN (2015)
With the imminent rise of aging offshore jacket platforms in Malaysia, decommissioning is assuming an integral role here. The decommissioning process per se is complex and marred with innumerable indeterminate risks associated with deteriorated structures and the practice of late-life decommissioning planning. The issue is further compounded by the absence of dedicated decision guidelines and appropriate local resources. As a way forward, this research proposes a decision aid toolkit as a management solution for asset owners to plan ahead and optimize the decommissioning decision making process. Integrating the benefits of Analytic Hierarchy Process (AHP) and an existing asset management system, the toolkit will provide a quantitative rating model to rank the most feasible decommissioning alternatives for selected assets. The developed model was tested with an existent industrial case study for validation and the associated results were in line with updated industrial best practices. A user-friendly framework presented herein carries a commercial value which provides for efficient usage of asset information and professional knowledge in containing decommissioning risk.